PENGARUH STRUKTUR KEPEMILIKAN DAN KOMITE AUDIT TERHADAP PERSISTENSI LABA - Misbakhul Munir Munir (Jurnal Ilmiah Akuntansi Peradaban, 2022)
This study was conducted to determine the effect of the relationship between the ownership structure consisting of institutional ownership, managerial ownership, ownership concentration and the effect of the audit committee on earnings persistence. The population in this study are manufacturing companies listed on the Indonesia Stock Exchange for the 2017-2020 period. The sampling technique used purposive sampling technique according to predetermined criteria, then the resulting research sample of 132 companies. The data analysis method in this study used multiple linear regression analysis with IBM SPSS software. The results of this study indicate that constitutional ownership has a significant positive effect on earnings persistence, managerial ownership has a significant positive effect, while the concentration of ownership and audit committee has no effect on earnings persistence. Keywords: Ownership structure, Audit Committee, earnings persistence